Analysis and exploration of popular photography concept under visual culture - Li, Shihao; Syed Alsagoff, Syed Agil; Adzharuddin, Nor Azura (Human Resource Management Academic Research Society, 2024)
Visual culture's undisputed place in today's society has been formed for a long time, rapid development, and it is surprising that people often think about how we today have visual elements in every corner of our senses, whether passive or active, people have become accustomed to this kind of life. As a very important part of visual culture, photography art has a unique growth track along with the development of contemporary art, which has brought a series of changes to the invasion of visual culture into people's lives. From 1839 to the present, through nearly two hundred years of history, he brings to the public is often the most intuitive feeling, the era of reading pictures along with the development of visual culture in the long years of human civilization. No matter what kind of photography, it is an important way to lead visual culture. What kind of experience does the general public have for photography as a visual art, what are the advantages and disadvantages, and what information can we get from it? How will the public's view of photography change with the change of visual culture?